Resting State Default Mode Network Connectivity, Dual Task Performance, Gait Speed, and Postural Sway in Older Adults with Mild Cognitive Impairment - Crockett, Rachel A.; Hsu, Chun Liang; Best, John R.; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2017)
Aging is associated with an increased risk of falling. In particular, older adults with mild cognitive impairment (MCI) are more vulnerable to falling compared with their healthy counterparts. Major contributors to this increased falls risk include a decline in dual task performance, gait speed and postural sway. Recent evidence highlights the potential influence of the default mode network (DMN), the frontoparietal network (FPN) and the supplementary motor area (SMA) on dual task performance, gait speed and postural sway. The DMN is active during rest and deactivates during task-oriented processes, to maintain attention and stay on task. The FPN and SMA are involved in top-down attentional control, motor planning and motor execution. The DMN shows less deactivation during task in older adults with MCI. This lack of deactivation is theorised to increase competition for resources between the DMN and task-related brain regions (e.g. the FPN and SMA), increasing distraction from the task and reducing task performance. However, no study has yet investigated the relationship between the between-network connectivity of the DMN with these regions and dual task walking, gait speed or postural sway. We hypothesised that greater functional connectivity both within the DMN and between DMN-FPN and DMN-SMA, will be associated with poorer performance during dual task walking, slower gait speed and greater postural sway in older adults with MCI. Forty older adults with MCI were measured on a dual task-walking paradigm, gait speed over a four-meter walk, and postural sway using a sway-meter. Greater within-DMN connectivity was significantly correlated with poorer dual task performance. Furthermore, greater inter-network connectivity between the DMN and SMA was significantly correlated with slower gait speed and greater postural sway on the eyes open floor sway task. Thus, greater resting state DMN functional connectivity may be an underlying neural mechanism for reduced dual task ability, slower gait speed and greater postural sway, resulting in the increased risk of mobility disability and falling in older adults with MCI.